Attacks against Rplin Iot: A Survey - Stephen, A; Arockiam, L (Annals of the Romanian society for cell biology, 2021)
The functionalities can be sensing, actuation, sharing information, analyzing and processing the sensed data.Since sensitive data are collected using IoT technology, the communication path should be secured. The attacks against RPL namely selective forwarding attack, sink hole attack, hello flood attack, wormhole attack, clone ID and Sybil attack were described, checked and implemented using Contiki and Cooja simulator. 2.2Sinkhole attack In [44], intrusion detection system was designed to detect sinkhole attack at edge level internet of thing environment. In the algorithm, a node will send the control message to the main base station before sending its data to its base station. [14] analyzed the existing techniques to detect sinkhole attack in wireless sensor network such as rule based, anomaly based detection, statistical method, hybrid based intrusion detection and key management.